The Role of XCR1 and its Ligand XCL1 in Antigen Cross-Presentation by Murine and Human Dendritic Cells - Kroczek, Richard A.; Henn, Volker (Frontiers in Immunology, 2012)
Recently, the chemokine receptor XCR1 has been found to be exclusively expressed on a subset of dendritic cell (DC) known to be involved in antigen cross-presentation. This review aims to summarize the known biology of the XCR1 receptor and its chemokine ligand XCL1, both in the mouse and the human. Further, any involvement of this receptor–ligand pair in antigen uptake, cross-presentation, and induction of innate and adaptive cytotoxic immunity is explored. The concept of antigen delivery to DC via the XCR1 receptor is discussed as a vaccination strategy for selective induction of cytotoxic immunity against certain pathogens or tumors.